Procedural issues of WTO dispute settlement system - Gony, Md Osman (KDI School, 2011)
Dispute settlement system of WTO is deemed to be the most effective forum to settle trade disputes between governments. WTO jurisprudence lacks exhaustive body of laws on evidence needed for discharging justice. Specially, on evidentiary matters WTO jurisprudence is silent. The adjudicators and contesting parties from different law family are in trouble in absence of threadbare rules on evidentiary matters. Not only the contesting parties, but also the adjudicators of the Panel and AB faces critical junctures in absence of complete code on evidence. The argument that other international courts as well do not have complete code on evidence1 is not tenable and based on real life judgment, as because, no other international court is dealing with cases having political as well as economic/trade implication. Moreover, almost every case of other international courts is different in nature from each other. In absence of wholesome code on evidence, over dependence on generally accepted principles, inherent power of the courts, jurisprudence of other international courts and jurisprudence developed by the AB is not good enough for a long lasting, sustainable as well as predictable adjudication system for multilateral trading system. However, DSU - being devoid of coordinated procedural details regarding evidence - is supplemented by some covered agreements having explicit laws on certain issues on evidence. Till then these few covered agreements are not well equipped as they provide some case/issue specific guidelines.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: WTO.